An Explorative Qualitative Study of Experiences and Challenges to Exclusive Breastfeeding Among Mothers in Rural Zimbabwe. (April 2015) - Nduna, Themba; Marais, Debbi; van Wyk, Brian
Breastfeeding is one of the most effective public health interventions known to reduce illness and deaths in infants and young children. While Zimbabwe has a breastfeeding culture, exclusive breastfeeding has remained low over the last decade. This study explored factors that enable and hinder exclusive breastfeeding in a rural district of Zimbabwe. Ten mothers and 5 key informants with breastfeeding experience were interviewed. Interviews were audiotaped, transcribed in Ndebele, translated into English, and analyzed using thematic analysis. Notable gaps still exist regarding mothers' understanding of exclusive breastfeeding. Hunger, myths, and traditional beliefs around breastfeeding, as well as mixed and inconsistent messages regarding HIV/AIDS and breastfeeding, remain barriers to exclusive breastfeeding in the study area. Support from significant others, good nutrition for the breastfeeding mother, and knowledge about breastfeeding emerged as factors enabling exclusive breastfeeding. Messaging on breastfeeding and HIV/AIDS need to be consistent. Breastfeeding messages ought to be context specific, targeting custodians of tradition and belief systems, including men and significant others, to create a supportive and enabling environment for mothers to exclusively breastfeed. Whether hunger and differences in breastfeeding patterns between boys and girls affect infant feeding practices warrants further research.